Functional Relationship Between Yeast VDAC Proteins and the Sak1 Protein Kinase in Activating the Snf1 Protein Kinase - (:unkn) unknown (My University, 2023)
In mammalian cells, the AMPK protein kinase regulates energy metabolism to ensure better survival in energy-depleting conditions. AMPK monitors the cellular energy state through the AMP-to-ATP ratio. Defects in the function of AMPK have been implicated in diseases such as diabetes, cancer, and obesity. Snf1 is the yeast ortholog of AMPK and is activated under conditions of energy stress through phosphorylation by upstream kinases, among which Sak1 is the primary one. When energy is abundant, Snf1 is dephosphorylated by protein phosphatases, among which the Reg1-Glc7 complex plays a primary role. Previous studies have suggested that the activation by upstream kinases and nuclear localization of Snf1 are regulated by mitochondrial voltage dependent anion channel (VDAC) proteins Por1 and Por2. VDACs are present in the mitochondrial outer membrane and conserved among eukaryotes. Por1 and Por2 physically interact with Snf1. Their presence in the outer membrane of mitochondria, the “powerhouse” of the cell, and the presence of binding sites for adenine nucleotides make them ideal candidates to sense cellular energy status and signal the activation of Snf1. In this study, we present genetic evidence that Por1 and Por2 contribute to the positive regulation of Snf1 by functioning in the same pathway as the primary Snf1-activating kinase, Sak1. Our findings may have implications for Snf1/AMPK regulation in other eukaryotes.